Study of Minimum Service Standard Index in Public Transportation: Sample of Trans Pakuan Bogor - Octadian Pratiwanggono; Rima Febrina (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
Public transportation in Bogor City is one of the issues that is still a concern and needs to be studied. Urban transportation management involves many strategic aspects and issues, such as reducing gas emissions, multimodal integration, and increasing public awareness and convenience to change the habits for using mass transportation. Buy the service program from BPTJ Ministry of Transportation through Trans Pakuan has been operating since November 2021 and during the operational period studies are still needed to achieve and improve service standards. This study uses field survey methods and quantitative analysis of the 8 dimensions of minimum service standards for mass transportation. The result shows that the Public Perception Service Index (Trans-Pakuan) shows